Gender, education and family dynamics in Jewish-American fiction: 1915-1930 - Harrison, Andrew (2023)
While the assimilationist novelists Abraham Cahan and Anzia Yezierska are usually considered to be part of a separate literary and political tradition to the communist writer and polemicist Michael Gold, their most enduring novels document the Jewish-American experience through the same thematic prisms: the conflict between Judaic and American gender norms, the quest of younger Jews to receive a fulfilling American education, and the fragile dynamics of the Lower East Side immigrant family. Considering Cahan’s The Rise of David Levinsky (1915), Yezierska’s Bread Givers (1925) and Gold’s Jews Without Money (1930) as complementary character portraits of vulnerable men and radical women counteracts the tendency to place them in competing streams of masculine and feminine fiction. Moreover, while scholars typically associate Gold with the 1930s proletarian tradition (thanks to his radical theories of cultural production), framing him as a canonical Jewish writer of the pre-Depression era reveals a consistent aesthetic thread between the bourgeois Bildungsroman and the radical proletarian novel. Treating these writers on a continuum with one another thus cements Gold’s reputation as a pioneering literary figure, and contributes to recent scholarship treating Cahan and Yezierska’s novels as more than just objects of historical nostalgia.